Analisis Penerapan Diversity, Equity, and Inclusion (DEI) dalam Menciptakan Lingkungan Kerja yang Berkeadilan: Kajian Literatur - Adelia Citra Erlansyah; Restu Paramasastra Nabila Pramesti; Alyaa Mahira; Anita Rismelani; Annisa Frizki; Dr. Arfian, S.Psi., M.Si (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Today's increasingly dynamic work environment encourages organizations not only to achieve organizational goals but also to foster a workplace that values diversity, promotes equity, and supports inclusion. This study aims to analyze the implementation of Diversity, Equity, and Inclusion (DEI) in creating a fair work environment while identifying its benefits and the challenges encountered during its implementation. This study employed a descriptive qualitative literature review by using secondary data obtained from scientific journals, books, and other relevant academic publications. The data were collected through a literature search using Google Scholar and analyzed by identifying, classifying, and interpreting findings from previous studies. The results indicate that the implementation of DEI contributes to the development of a more open, equitable, and respectful work environment. Well-managed diversity encourages creativity and innovation, while the principles of equity and inclusion improve job satisfaction, employee engagement, and interpersonal relationships among employees. However, the implementation of DEI continues to face several challenges, including stereotypes, unconscious bias, and the lack of consistent organizational commitment to integrating DEI values into workplace policies and practices. Therefore, the successful implementation of DEI requires committed leadership, clear organizational policies, and a workplace culture that values diversity in order to create a productive, harmonious, and sustainable work environment.